A development of a cancer information system by using information retrieval techniques / Tan Chee Ming - Tan, Chee Ming (2006)
This project has being specifically focuses on the development of a Cancer Information System by using information retrieval (IR) techniques. In this regards, this project tends to produce a prototype system to provide user with two types of cancer information, specifically breast cancer and lung cancer, and a category called “general cancer” that discusses the common characteristics regarding cancer disease. The system consists of two parts; the Web-based search engine and the documents collection stored in local file systems. Despite traditional hyperlinks method of Website navigation, the system enables user to search for information by entering natural language query. The query will be processed by the information search engine and then return a maximum of six most relevant documents that possibly contains the information requested by the user. User can then browse any of these documents for detail information.